2018
DOI: 10.1186/s12575-018-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Non-small-Cell Lung Cancer with Qi-Nourishing Essence-Replenishing Chinese Herbal Medicine Combined with Chemotherapy

Abstract: BackgroundTo evaluate the effect of qi-nourishing essence-replenishing Chinese herbal medicine combined with chemotherapy in survival of advanced non-small-cell lung cancer(NSCLC) patients with essence and qi deficiency.MethodsA prospective multi-centered randomized controlled study was conducted, and 266 advanced NSCLC patients were enrolled. 126 patients in control group received Vinorelbine plus cisplatin(NP) chemotherapy combined with symptom-oriented Chinese herbs medication(without qi-nourishing essence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…All the eligible studies were conducted in China, with four articles published in English [9–11, 13] and the rest in Chinese [8, 12, 14–20]) (Table 1). In this study, there are 6 related lung cancers [9–11, 14, 19, 20], 3 related to Leukemia [12, 17, 18], 3 related to Liver cancer [8, 15, 19], one related to breast or colon cancer [13], and one related to gastric cancer [17] (Table 2). Because leukemia is a kind of malignant clonal disease of hematopoietic stem cells and belongs to the category of cancer, this study also included the research of leukemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the eligible studies were conducted in China, with four articles published in English [9–11, 13] and the rest in Chinese [8, 12, 14–20]) (Table 1). In this study, there are 6 related lung cancers [9–11, 14, 19, 20], 3 related to Leukemia [12, 17, 18], 3 related to Liver cancer [8, 15, 19], one related to breast or colon cancer [13], and one related to gastric cancer [17] (Table 2). Because leukemia is a kind of malignant clonal disease of hematopoietic stem cells and belongs to the category of cancer, this study also included the research of leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 RCTs with Overall response rate (RR) [8, 10–12, 14–19], 8 RCTs of them showed that Danshen formulae improved RR [10–14], and 2 RCTs suggested that Danshen formulae did not significantly improve RR [8, 11]. In 5 RCTs with survival rates, 4 RCTs of them indicated that Danshen Formulae improved survival rates [9, 15, 18, 20] and 1 RCT indicated that Danshen formulae did not significantly improve RR [8]. Seven RCTs were with side effects [10, 12–15, 17, 20] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with metastatic NSCLC, platinum-based chemotherapy combined with TCM was reported to significantly decrease the incident of nausea and vomiting, improve ECOG from 69 to 90% and show a better QoL variables score calculated by FACT-L subscales (Guo et al, 2017 ; Liao et al, 2017 ). Moreover, our previous studies have shown that CHMF enhances the chemotherapeutic effect, improve QoL and reduce the adverse effects of platinum-contained chemotherapeutics on NSCLC patients (Jiao et al, 2017 ; Wang et al, 2017 ; Gong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), which is characterized by multiple compounds, targets, and pathways, has been widely combined with chemotherapy against NSCLC [12] [13] [14] [15]. TCM can not only relieve chemotherapy-related side effect but also prolong the survival time of patients [16].…”
mentioning
confidence: 99%